2013
DOI: 10.1111/gcb.12279
|View full text |Cite
|
Sign up to set email alerts
|

Regional decline in growth rates of massive Porites corals in Southeast Asia

Abstract: This study reports the first well-replicated analysis of continuous coral growth records from warmer water reefs (mean annual sea surface temperatures (SST) >28.5 °C) around the Thai-Malay Peninsula in Southeast Asia. Based on analyses of 70 colonies sampled from 15 reefs within six locations, region-wide declines in coral calcification rate (ca. 18.6%), linear extension rate (ca. 15.4%) and skeletal bulk density (ca. 3.9%) were observed over a 31-year period from 1980 to 2010. Decreases in calcification and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
80
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 50 publications
7
80
2
1
Order By: Relevance
“…This is also confirmed, with the opposite effect reported on coral communities located in the tropical zone, where coral growth has decreased 11–21% associated with the steady increment of the SST (Cooper et al, 2008; De’ath, Lough & Fabricius, 2009; Tanzil et al, 2013; Ridd, Da Silva & Stieglitz, 2013). The SST keeps the organism on the limit of their thermal threshold and consequently decrease or inhibit the coral growth.…”
Section: Discussionsupporting
confidence: 66%
“…This is also confirmed, with the opposite effect reported on coral communities located in the tropical zone, where coral growth has decreased 11–21% associated with the steady increment of the SST (Cooper et al, 2008; De’ath, Lough & Fabricius, 2009; Tanzil et al, 2013; Ridd, Da Silva & Stieglitz, 2013). The SST keeps the organism on the limit of their thermal threshold and consequently decrease or inhibit the coral growth.…”
Section: Discussionsupporting
confidence: 66%
“…This observation is consistent with multiple studies that have reported marked decreases in coral growth over the past few decades, including data from the Great Barrier Reef (Cooper et al, 2008;De'ath et al, 2009), Red Sea (Cantin et al, 2010), Belize (Castillo et al, 2011), Andaman Sea (Tanzil et al, 2009), the Thai-Malay Peninsula (Tanzil et al, 2013), and Panama (Manzello, 2010). On many of these reefs, declining trends in growth have been linked to increasing SST, suggesting that ocean warming may have already produced temperatures that surpass the thermal thresholds of many reef-building corals worldwide.…”
Section: Discussionsupporting
confidence: 92%
“…A 30% decrease in linear extension rate since 1998 has also been detected in Diploastrea corals in the Red Sea [30]. A region-wide 19% decline in Porites calcification rates between 1980 and 2010 has recently been reported across six locations of the Thai-Malay Peninsula of southeast Asia [31]. Several studies which re-measured (i.e.…”
Section: Introductionmentioning
confidence: 92%